1997
DOI: 10.1183/09031936.97.10061372
|View full text |Cite
|
Sign up to set email alerts
|

Current aspects of spontaneous pneumothorax

Abstract: In spite of the fact that blebs and bullae are frequently found in patients with primary spontaneous pneumothorax, they seldom seem to be the actual cause of the pneumothorax. Inflammatory changes in the distal airways play an important role in the occurrence of the pneumothorax during transpulmonary pressure changes.The value of the routine use of additional expiratory chest radiographs in diagnosing pneumothoraces has been doubted in previous studies. In this review, the diagnostic yield from additional expi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
164
2
27

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 292 publications
(200 citation statements)
references
References 71 publications
4
164
2
27
Order By: Relevance
“…16) Although emphysema-like changes were seen in 81% of patients with PSP, no association with PAL or recurrence could be demonstrated. 17) In a publication of the British Thoracic Society in 2003 and 2010, smoking, height and age over 60 years have been reported as an independent risk factors for the recurrences in PSP. 1,18) Potential ipsilateral recurrences or PAL might be thought to be more frequent in patients with total lung collapse since the defect has been reported to be larger in such patients.…”
Section: Discussionmentioning
confidence: 99%
“…16) Although emphysema-like changes were seen in 81% of patients with PSP, no association with PAL or recurrence could be demonstrated. 17) In a publication of the British Thoracic Society in 2003 and 2010, smoking, height and age over 60 years have been reported as an independent risk factors for the recurrences in PSP. 1,18) Potential ipsilateral recurrences or PAL might be thought to be more frequent in patients with total lung collapse since the defect has been reported to be larger in such patients.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiologic data are mainly based on a small number of studies, which seemingly show an incidence of 18-28/100.000 cases yearly in men and 1.2-6/100.000 cases yearly in women, respectively [5,6]. No other large-scale studies are available to date, so that a significant part of the epidemiologic knowledge is derived from case series, often showing contradictory figures [7][8][9][10]. Regardless of the still partially undefined epidemiology, SP apparently displays a bimodal peak frequency.…”
Section: Introductionmentioning
confidence: 99%
“…In two case-control studies, the CT scans of persons with recent PSP (including nonsmokers) were found to have significantly more emphysema-like changes in both studies as well as a lower mean radiographic density of the lungs in one of the studies (9,10). A CT study and multiple surgical studies have consistently identified blebs and bullae in patients suffering a spontaneous pneumothorax (11)(12)(13)(14)(15)(16). Secondary spontaneous pneumothorax occurs in patients with clinically apparent lung disease, which is most commonly COPD (2,17,18).…”
mentioning
confidence: 99%